1999
DOI: 10.1136/bmj.318.7196.1456
|View full text |Cite
|
Sign up to set email alerts
|

Advising parents of asthmatic children on passive smoking: randomised controlled trial

Abstract: Objective To investigate whether parents of asthmatic children would stop smoking or alter their smoking habits to protect their children from environmental tobacco smoke. Design Randomised controlled trial. Setting Tayside and Fife, Scotland. Participants 501 families with an asthmatic child aged 2-12 years living with a parent who smoked. Intervention Parents were told about the impact of passive smoking on asthma and were advised to stop smoking or change their smoking habits to protect their child's health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 23 publications
0
68
0
3
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23] Only from 1 of those studies was a sustained reduction in exposure to environmental tobacco smoke, measured as cotinine levels, reported, and from another study a significant reduction in the number of unscheduled asthma visits was reported. 12,13 Collectively, these trials raise serious questions about whether it is prudent to continue to rely on anticipatory guidance to reduce children's exposure to tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20][21][22][23] Only from 1 of those studies was a sustained reduction in exposure to environmental tobacco smoke, measured as cotinine levels, reported, and from another study a significant reduction in the number of unscheduled asthma visits was reported. 12,13 Collectively, these trials raise serious questions about whether it is prudent to continue to rely on anticipatory guidance to reduce children's exposure to tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…11 Numerous studies have tested the efficacy of anticipatory guidance to reduce SHS exposure for children, but the majority failed to show significant reductions in children's SHS exposure by using measurements of cotinine, a metabolite of nicotine, or improvements in asthma symptoms. [12][13][14][15][16][17][18][19][20][21][22][23] This problem might be overcome if there was a technology to reduce SHS exposure passively, such as highefficiency, particulate-arresting (HEPA) air cleaners.…”
mentioning
confidence: 99%
“…Finally, a study by Irvine et al 40 examining exposure to ETS among asthmatic children in Scotland also failed to produce significant effects for a counseling intervention. Subjects for this study were families identified through the health care system as having an asthmatic child and at least 1 parent who smokes.…”
Section: Reducing Ets Exposure Health Effects Of Ets On Childrenmentioning
confidence: 99%
“…Désirée Larenas-Linnemann, 1 Jorge Salas-Hernández, 2 Juan Carlos Vázquez-García, 3 Ignacio Ortiz-Aldana, 4 Margarita Fernández-Vega, 5 Blanca Estela Del Río-Navarro, 6 María del Carmen Cano-Salas, 7 Jorge Agustín Luna-Pech, 8 José Antonio Ortega-Martell, 9 Jade Romero-Lombard, 10 Erika del Carmen López-Estrada, 11 Jimena Villaverde-Rosas, 12 José Luis Mayorga-Butrón, 13 Mario Humberto Vargas-Becerra, 14 Martín BedollaBarajas, 15 Noel Rodríguez-Pérez, 16 Ambrocio Aguilar-Aranda, 17 Carlos Adrián Jiménez-González, 18 Carlos García-Bolaños, 19 Claudia GarridoGalindo, 20 David Alejandro Mendoza-Hernández, 21 Enrique Mendoza-López, 22 Gerardo López-Pérez, 21 Guillermo Hideo Wakida-Kuzonoki, 23 Héctor Hernán Ruiz-Gutiérrez, 24 Héctor León-Molina, 25 Héctor Martínez-De la Lanza, 26 Héctor Stone-Aguilar, 27 Javier Gómez-Vera, 28 Jorge…”
unclassified